The big family - Lingping, Huang; Shengwei, Zhu; Guangxi Television Station (China : Guangxi Television Station, 2006)
The Big Family traces the life of a traditional peasant family facing new economic rules. It is the story of the Zhou family who are well known in their small farming community in the heart of China
Executive producer, Huang Zhucheng, Peng El, Michel Noll ; editing, Zhong Yan, Liang Jin, Cecila Beaulaude
Narration: Carol Drinkwater
DVD format
In English and Chinese with English subtitles
Chinese language in English translation
Keywords: Rural families -- China; Peasants -- China; Father and child -- China